Pre-conceptional Maternal Vitamin B12 Supplementation Improves Offspring Neurodevelopment at 2 Years of Age: PRIYA Trial - D'souza, Naomi; Behere, Rishikesh V.; Patni, Bindu; Deshpande, Madhavi; Bhat, Dattatray; Bhalerao, Aboli; Sonawane, Swapnali; Shah, Rohan; Ladkat, Rasika; Yajnik, Pallavi; Bandyopadhyay, Souvik K.; Kumaran, Kalyanaraman; et al. (Frontiers in Pediatrics, 2021)
Background: The first thousand days window does not include the pre-conceptional period. Maternal pre-conceptional health has a profound influence on early embryonic development. Nutrition provided by B-complex vitamins is important for fetal growth, especially neural development. We report effects of a maternal pre-conceptional vitamin B12 and multi micronutrient (MMN) supplementation on offspring neurodevelopment. Methods: In the Pune Rural Intervention in Young Adolescents trial (PRIYA), adolescents (N=557, 226 females) were provided with vitamin B12 (2μg/day) with or without multiple micronutrients, or a placebo, from preconception until delivery. All groups received mandatory iron and folic acid. We used the Bayley’s Scale of Infant Development (BSID-III) at 24-42 months of age to investigate effects on offspring neurodevelopment. Results: Participants had similar baseline B12 levels. The levels improved in the B12 supplemented groups during pre-conception and pregnancy (28 weeks gestation), and were reflected in higher cord blood holotranscobalamin (holo-TC) levels compared to the placebo group. Neurodevelopmental outcomes in the B12 alone group (n=21) were better than the placebo (n=27) in cognition (p=0.044) and language (p=0.020) domains (adjusted for maternal baseline B12 levels). There was no difference in neurodevelopmental outcomes between the B12+MMN (n=26) and placebo group. Cord blood Brain Derived Neurotrophic Factor (BDNF) levels were highest in the B12 alone group, though not significant. Conclusion: Pre-conceptional vitamin B12 supplementation improved maternal B12 status and offspring neurodevelopment at 2 years of age. The usefulness of cord BDNF as a marker of brain development needs further investigation. Our results highlight the importance of intervening during pre-conception.